2013
DOI: 10.1111/trf.12509
|View full text |Cite
|
Sign up to set email alerts
|

A new bead‐based human platelet antigen antibodies detection assay versus the monoclonal antibody immobilization of platelet antigens assay

Abstract: For the vast majority of the specimens tested (93%) the results of the PAKLx were in concordance with the MAIPA. The PAKLx is a fast, easy to perform, and sensitive PLT antibody screening method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 11 publications
(12 reference statements)
1
33
0
Order By: Relevance
“…Other techniques are also possible to use. For instance, different Luminex bead-based assays for the detection of anti-HPA-1a antibodies have been tested and are used by some 62. Furthermore, low-avidity anti-HPA-1a antibodies may be detected using surface plasmon resonance technology 63…”
Section: Diagnosismentioning
confidence: 99%
“…Other techniques are also possible to use. For instance, different Luminex bead-based assays for the detection of anti-HPA-1a antibodies have been tested and are used by some 62. Furthermore, low-avidity anti-HPA-1a antibodies may be detected using surface plasmon resonance technology 63…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, the performance of a commercial, bead‐based ACE assay, PAKLx, was compared with the MAIPA by two groups . PAKLx design differs from the PABA, in that beads are supplied with individual platelet GPs already captured by specific monoclonal antibodies, and patient sera are simply incubated with the bead mixture for platelet antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several different antigen‐capture assays for the detection of platelet antibodies have been reported that use polystyrene beads instead of wells of polystyrene microplates to capture platelet GPs, including a bead version of the MAIPA and a commercial bead version of the ACE . We have now developed the platelet antibody bead array (PABA), which is a bead version of the MACE but with a fluorescent antibody detection endpoint instead of ELISA.…”
mentioning
confidence: 99%
“…Women carrying an HPA‐1a‐positive fetus should be examined for HPA‐1a antibodies at regular intervals during pregnancy, for instance every 4–6 weeks. Examination for anti‐HPA‐1a antibodies has until recently been technically challenging, but this analysis can today be performed easily using a newly developed bead‐based platelet antibody‐detecting assay (Pak Lx™, Immucor) . Women with HPA‐1a antibodies should be referred to a specialized centre for maternal‐fetal medicine for close follow‐up and risk stratification.…”
Section: How Could Screening For Fnait Be Conducted and What Could Bementioning
confidence: 99%